A mixed-methods study of the Care Needs of individuals with idiopathic Pulmonary fibrosis and their carers—CaNoPy: a study protocol. Issue 8 (7th August 2013) - Byrne, Anthony; Sampson, Cathy; Baillie, Jessica; Harrison, Kim; Hope-Gill, Ben; Hubbard, Richard; Griffiths, Gareth; Nelson, Annmarie
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a progressive, life-threatening illness of unknown aetiology, with no proven pharmacological treatments. There is a limited evidence base indicating that the disease negatively affects quality of life, leading to increased dependence, restrictions on daily activities and fatigue. However, there is a paucity of in-depth information on disease impact across its trajectory, particularly in relation to unmet needs, outcomes of importance to patients and the experiences of carers. Furthermore, little is known about the support and information needs of individuals and their carers, or at what point individual need should trigger a referral to palliative care services. Methods and analysis: A mixed-methods study is proposed recruiting individuals with IPF at different stages of the disease and their carers from three respiratory centres in England and Wales. In-depth interviews will be undertaken with participants, adopting an Interpretative Phenomenological Analysis approach. The study will also use validated questionnaires to explore quality of life (EQ-5D), depression (Hospital Anxiety and Depression Scale), breathlessness (Borg dyspnoea scale) and cough (Leicester Cough Questionnaire, Cough Symptom Score). Ethics and dissemination: Ethical approvals were gained in April 2012. Palliative care research is a developing field, but there has been limited focus on IPF. We anticipate that the results of the study will enable healthcare professionals to provide appropriate palliative care across the trajectory for individuals with the disease, and their carers, and we therefore aim to disseminate via relevant respiratory and palliative care journals and conferences. We will also support the lay representative involved in the project to disseminate the findings to patient groups.